Ce-induced NiS bifunctional catalyst transformation: enhancing urea oxidation coupled with hydrogen electrolysis - Zhang, Yingzhen (2024)
The treatment of urea-containing wastewater is crucial for sustainable environmental development, given its low theoretical thermodynamic barrier (0.37 V), which can effectively replace the OER process in water electrolysis and enhance hydrogen production efficiency. Nevertheless, designing dual-functional catalysts capable of effectively performing catalytic tasks remains a challenge. Herein, in this work a cerium-doped nickel sulfide (Ce-NiS) catalyst is synthesized by an electrodeposition method, which is used as a bifunctional catalyst for electrolytic hydrogen production from urea-containing wastewater. Ce-NiS exhibits a higher Faradaic efficiency (FE, 91.39%) compared to NiS (67.52%) for hydrogen production from simulated urea-containing wastewater. In situ Raman spectroscopy reveals that Ce doping induces the reconstruction of NiS into high-valence nickel species (NiOOH), which is considered the actual active center for the electrochemical UOR process. Notably, the apparent electrochemical activation energy for the UOR decreased from 8.72 kJ mol−1 (NiS) to 5.68 kJ mol−1 (Ce-NiS), indicating that doping with Ce significantly reduces the energy barrier for the UOR and enhances the catalytic urea oxidation capability. This study employs a strategy of rare-earth metal (Ce) doping to enhance the efficiency of urea-coupled electrolytic hydrogen production, providing promising insights for energy recovery from urea-containing wastewater and the development of high-performance dual-functional catalysts.